COST INFORMATION SYSTEM AND OPERATIONS MANAGEMENT IN AN INDUSTRIAL MAINTENANCE MIPYME - Colquicocha Carrascal, Javier Rey (2021)
Objective: To evaluate the incidence of a cost information system in the management of operationsin a MSME for industrial maintenance of electric motors. Method: in this case study, indicatormeasurements are collected based on 179 repair services completed during the 12 periods of2017, which were estimated with the current cost information system and then compared withthose obtained by applying an improved design. Results: It was found that the improved designsignificantly affects the proposed indicators when compared with the current system. Conclusions:The adoption of the improved design could avoid the implementation of wrong policies or rejectservices that could be profitable due to the cross-subsidy found when comparing both systems.